2019
DOI: 10.1177/0020764019839082
|View full text |Cite
|
Sign up to set email alerts
|

Rates and correlates of employment in patients with schizophrenia: A multicenter study in Turkey

Abstract: Background: There is not enough information regarding the participation in the working life of the patients with schizophrenia in Turkey. Aims: The aim of this study was to examine the occupational experiences of patients with schizophrenia before and after the illness and to investigate the factors that predict work participation. Methods: The data on occupational life of the patients with schizophrenia, which were treated as outpatients in six different centers, were examined. The rates of participation in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
2
1
2
Order By: Relevance
“…Although in the univariate analysis, the HF group had a significantly shorter duration of the disorder than the LF group, when we included this variable in the logistic regression together with the rest of the variables, it was not retained in the model. Our result contradicts several studies that found an association between longer disease duration and poorer functioning (56, [67][68][69][70][71][72]. This discrepancy fuels the debate about whether longer illness duration is invariably and unequivocally associated with poorer functioning in people with schizophrenia.…”
Section: Protective and Risk Factors For Low Functioningcontrasting
confidence: 99%
“…Although in the univariate analysis, the HF group had a significantly shorter duration of the disorder than the LF group, when we included this variable in the logistic regression together with the rest of the variables, it was not retained in the model. Our result contradicts several studies that found an association between longer disease duration and poorer functioning (56, [67][68][69][70][71][72]. This discrepancy fuels the debate about whether longer illness duration is invariably and unequivocally associated with poorer functioning in people with schizophrenia.…”
Section: Protective and Risk Factors For Low Functioningcontrasting
confidence: 99%
“…Echoing existing evidence (Ang et al, 2020;Honkonen et al, 2007;Nordt et al, 2007), sex did not emerge as a significant predictor of NEET status. As participants in the present study were all recruited from Canada, this result could reflect a contextual and cultural divergence in comparison to a study conducted in Turkey which suggested being male predicted being in employment after the onset of schizophrenia spectrum disorders (Yildiz et al, 2019). Our result also resembled the conclusion drawn from a recent meta-analysis in which no gender-based pattern was found in the relationship between being NEET and mental health challenges (Gariépy et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…Most current literature that examined factors associated with NEET status in people living with psychosis took one-dimensional approaches, looking at the separate effects of social and clinical factors on NEET. These studies frequently indicated lower rates of NEET status in younger individuals (Honkonen et al, 2007;Salkever et al, 2007;Üçok et al, 2012;Wewiorski & Fabian, 2004) or males (Ang et al, 2020;Salkever et al, 2007;Üçok et al, 2012;Yildiz et al, 2019). However, a few studies did not find sex differences in NEET status (Honkonen et al, 2007;Nordt et al, 2007) or reported conflicting results suggesting that NEET participants were more likely to be male (Iyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Şizofreni hastalarının iş yaşamına katılımı her yaş grubunda düşük olup genellikle %10-30 arasında bildirilmektedir. 7,8 Bu düşük orana rağmen, hastaların önemli bir kısmı iş yaşamında olmayı yeğlemekte ve iş arayışında bulunmaktadır. [9][10][11] Çalışma yaşamına katılımın önünde, bireysel özellikler, hastalığın süreğenliği, içselleştirilmiş damgalama, profesyonellerin ve işverenlerin olumsuz tutumları, ayrımcılık, sosyal yardımların kesilmesiyle ilgili endişeler, işe geri dönüş sürecinde destek hizmetlerinin eksikliği gibi engeller olduğu görülmektedir.…”
Section: Introductionunclassified
“…27 Çalışma yaşamında olan hastaların bir kısmı rekabetçi işlerde çalışırken çoğunluğu yarı zamanlı işlerde, yakınlarının desteğindeki işlerde ya da engelli kadrosundan ayrılmış işlerde çalışmaktadır. 8,28,29 Türkiye'de gündüz hastaneleri, sivil toplum kuruluşları ve toplum ruh sağlığı merkezlerinde (TRSM) şizofreni hastaları için korumalı işyeri ya da iş uğraş tedavisi çerçevesinde kısa süreli geleneksel mesleki iyileştirim çalışmalarının yapıldığı bilinmektedir. Kocaeli Üniversitesi Gündüz Hastanesi'nde galoş üretimi yapılarak hastaların gelir elde etmesi sağlanmış, Bolu TRSM bünyesindeki kafeteryada hastalar dönüşümlü olarak çalıştırılmış, Şizofreni Dernekleri Federasyonu tarafından şizofreni hastalarının çalışması için korunaklı iş ortamı olarak açılan Mavi At Kafe'de hastaların çalışması sağlanmıştır.…”
Section: Introductionunclassified